Pelatihan Pembuatan Brownies Berbahan Dasar Tepung Mocaf di Desa Limpakuwus - Lestari, Hanis Adila; Erminawati, Erminawati; Farisi, Herdian; Aini, Nur; Astuti, Santi Dwi; Istiqomah, Istiqomah; Luhsarandini, Bivannie; Nugroho, Adityo (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Cassava is one of the abundant tubers in Limpakuwus Village. In its development, to increase its selling value, cassava can be processed into mocaf flour (modified cassava flour). In previous community service, the local community had received training related to making mocaf flour. Therefore, further training was conducted to process mocaf flour into bakery products. One of them was making mocaf brownies because they were considered simple and easy. The purpose of this service was to enhance the skills of PKK mothers in processing mocaf flour into mocaf brownies and provide motivation for forming small business groups and promoting entrepreneurship. The implementation method began with identifying problems and potential in the village, followed by coordination and planning of activities, and the implementation of training and evaluation. Based on the results of the service carried out for PKK mothers in Limpakuwus Village, it showed that participants were able to process mocaf flour into mocaf brownies and had a positive impact.